Sensorimotor impairments during spaceflight: Trigger mechanisms and haptic assistance - Weber, Bernhard; Stelzer, Martin (Frontiers in Neuroergonomics, 2022)
In a few years, manned space missions are planned in which the sensorimotor performance of humans will be of outstanding importance. However, research has repeatedly shown that human sensorimotor function can be impaired under conditions of microgravity. One way to compensate for these impairments is haptic feedback provided by the human-machine interface. In the current series of studies, sensorimotor performance was measured in basic aiming and tracking tasks. These tasks had to be performed using a force feedback joystick with different haptic settings (three spring stiffnesses, two dampings, two virtual masses, and no haptics). In two terrestrial studies, we investigated (1) the effects of cognitive load on performance in a dual-task paradigm (N = 10) and (2) which learning effects can be expected in these tasks in a longitudinal study design (N = 20). In the subsequent space study (N = 3 astronauts), the influence of microgravity and haptic settings of the joystick were investigated. For this purpose, three mission sessions after 2, 4, and 6 weeks on board the International Space Station (ISS), as well as terrestrial pre- and post-flight sessions, were conducted. The results of the studies indicated that (1) additional cognitive load led to longer reaction times during aiming and increased tracking error while aiming precision was not affected. (2) Significant learning effects were evident for most measures in the study on time effects. (3) Contrary to the expected learning trend, microgravity impaired the aiming precision performance of all astronauts in the initial phase of adaptation (2 weeks in space). No other significant effects were found. Intriguingly, these performance decrements could be compensated for with low to medium spring stiffness and virtual mass. The general result pattern provides further evidence that distorted proprioception during early adaptation to microgravity conditions is one main mechanism underlying sensorimotor impairment.